Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China. Issue 6 (18th August 2019) - Zhu, Hong; Yi, Xian-GUI; Li, Yong-Fu; Zhu, Shu-Xia; Li, Meng; Duan, Yi-Fan; Wang, Xian-Rong
Abstract : Cerasus dielsiana (Rosaceae) is one of the most characteristic wild flowering cherry species endemic to subtropical China, with high conservation value from ornamental, economic, and ecological perspectives. To verify its spatial genetic structure and phylogeographic history, evaluation of nuclear (ITS) sequence variation in 203 individuals from 25 wild populations across its natural distribution ranges was conducted. High levels of ribotypes and nuclear diversity ( H d = 0.879 ± 0.012, π = 3.56 ± 0.16) were detected at the species level. Spatial analysis of molecular variation (SAMOVA), median-joining network and phylogenetic Neighbour-joining tree assigned the populations into four genetically distinct groups. Meanwhile, high levels of genetic differentiation among populations and strong phylogeographic patterns ( N st = 0.837 > G st = 0.585; P < 0.05) were revealed based on the analysis of molecular variance (AMOVA). Results of neutrality tests, mismatch distribution analyses, Mantel test, barrier analyses, together with ecological niche modelling (ENM) simulation and BEAST analysis suggest a long-term demographic history (95% HPD: 3.64–8.83 Mya) of C. dielsiana, and at least three potential in situ glacial refugia as well as recent demographic expansion in eastern region have been detected. Collectively, we highlight that the combined effect of natural selection and random genetic drift under complex topography and palaeoclimatic oscillations since the Last Glacial Maximum (LGM) in subtropical China might have been the main driver to the species' allopatric differentiation. Scientific conservation and sustainable utilization for wild C. dielsiana germplasm resources were subsequently proposed.